A review of near field communication process: how do it works? - Brohi, Imtiaz Ali; Shaikh, I. A; Katper, Naveeda Karim; Maher, Zulfikar Ahmad; Channar, Sheeba Hussain; Shah, Asadullah (University of Sindh, 2018)
Living in digital era and surrounding with intelligent devices has made things easy for us, But we are still looking for ways to make the mainstay of human living easy so that it can be made without wasting time and energy. Monetary transactions are mostly done under the same conventional system in developed and developing countries. While few countries have successfully adopted new trends and development in the MP systems and with the introduction of Near Filed Communication (NFC) technology which is around for more than a decade and almost showing everywhere nowadays due to its convenience and mobility. NFC technology has paved a track for secure and fastest MP technology. In this paper the authors have discussed the type of tags, modes of operation, and usage of NFC for different purpose.